The effects of the EU equal-treatment legislation Directive for fixed-term workers: Evidence from the UK - Andrea Salvatori (University of Essex, Institute for Social and Economic Research (ISER), 2014)
In 2002, the United Kingdom implemented the EU directive mandating equal treatment of fixed-term and permanent workers. This paper uses eleven years of data from the Labour Force Survey to assess whether the new legislation has led to a decrease in the average wage gap between fixed-term and permanent workers. For women, there is no evidence of that. For men, the wage gap appears to have closed after 2002. However, this gap was falling even before 2002 and some evidence of changes in the selection of workers after the implementation of the Directive cast doubts on the extent to which the closing of the gap can be ascribed to the new legislation.
Keywords: J3; J7; J41; 330; fixed-term contracts; wage differentials; equal-treatment legislation